Price effects of horizontal mergers: A retrospective on retrospectives - Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
In this comprehensive review of ex-post merger studies price effects of horizontal transactions are evaluated. By combining and further analyzing the results of 52 retrospective studies on 82 mergers or merger-like transactions it can be shown that the industry alone is no strong indication for the direction of price-related merger effects. However, the "size" or "importance" of a transaction as well as market concentration pre-merger and change in concentration due to the transaction seem to have an impact on post-transaction price development.
Keywords: D49; K21; L13; L40; 330; Antitrust; Merger Control; Industrial Economics; Retrospective Studies; Ex-Post Studies; Competition Law Enforcement